Can macroeconomists forecast risk? Event-based evidence from the euro area SPF - Geoff Kenny; Thomas Kostka; Federico Masera (European Central Bank (ECB), 2013)
We propose methods to evaluate the risk assessments collected as part of the ECB Survey of Professional Forecasters (SPF). Our approach focuses on direction-of-change predictions as well as the prediction of relatively more extreme macroeconomic outcomes located in the upper and lower regions of the predictive densities. For inflation and GDP growth, we find such surveyed densities are informative about future direction of change. Regarding more extreme high and low outcome events, the surveys are really only informative about GDP growth outcomes and at short-horizons. The upper and lower regions of the predictive densities for inflation are much less informative.
Keywords: C22; C53; 330; calibration error; forecast evaluation; probability forecasts; Survey of Professional Forecasters